2009
DOI: 10.1016/j.cmet.2009.09.009
|View full text |Cite
|
Sign up to set email alerts
|

FXR Acetylation Is Normally Dynamically Regulated by p300 and SIRT1 but Constitutively Elevated in Metabolic Disease States

Abstract: Summary The nuclear bile acid receptor FXR is critical for regulation of lipid and glucose metabolism. Here we report that FXR is a target of SIRT1, a deacetylase that mediates nutritional and hormonal modulation of hepatic metabolism. Lysine 217 of FXR is the major acetylation site targeted by p300 and SIRT1. Acetylation of FXR increases its stability but inhibits heterodimerization with RXRα, DNA binding, and transactivation activity. Down-regulation of hepatic SIRT1 increased FXR acetylation with deleteriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
342
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 282 publications
(363 citation statements)
references
References 39 publications
16
342
2
3
Order By: Relevance
“…6E). In addition to regulation through the Sirt1-FXR pathway (20), the Sirt1-FoxO1 pathway also plays an important role in the regulation of the Nr0b2 gene expression. As an orphan nuclear receptor, Nr0b2 has been shown to inhibit numerous nuclear receptors and transcription factors, including HNF-4␣, CREB, and FoxO1 (4,5,23,33,47).…”
Section: Discussionmentioning
confidence: 99%
“…6E). In addition to regulation through the Sirt1-FXR pathway (20), the Sirt1-FoxO1 pathway also plays an important role in the regulation of the Nr0b2 gene expression. As an orphan nuclear receptor, Nr0b2 has been shown to inhibit numerous nuclear receptors and transcription factors, including HNF-4␣, CREB, and FoxO1 (4,5,23,33,47).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the activation of SIRT1 by resveratrol substantially decreased the acetylated FXR levels in the livers of ob/ob mice. In addition, treatment with resveratrol significantly decreased the Shp mRNA levels and elevated the bile acid pool sizes in mice [38] . Our results confirmed that resveratrol enhanced the expression of transporters and enzymes correlated with elevated FXR levels in vivo.…”
Section: Wwwchinapharcom Wang T Et Almentioning
confidence: 99%
“…Through these domains, p300 and CBP interact with basal transcription factors and RNA polymerase II as well as a variety of other transcription factors to function as scaffold proteins facilitating interactions among the basal transcription machinery and upstream transcription factors (8 -11). The histone acetyltransferase activity of p300 and CBP modifies histones leading to chromatin remodeling and transcriptional activation; p300 and CBP also acetylate other proteins such as FXR, SREBP-1, CRTC2, and FOXO1, leading to the changes of genes related to glucose and lipid metabolism (12)(13)(14)(15). Gene alterations in CBP and p300 cause various diseases such as Rubinstein-Taybi syndrome and leukemia (8, 16 -18).…”
mentioning
confidence: 99%